Diagnosis of medical errors and the responsibility of nursing staff reported in Sadr Teaching Hospital - محمد اياد طاهر; محمد امجد هاشم (Journal of Economics and Administrative Sciences, 2015)
The study aims to determine the responsibility of nursing staff for medical errors that accompany the surgery at the hospital , which is one of the important issues that the importance of determining the responsibility of landlords nursing medical errors in the hospital was the rationale in choosing the subject. Since study included cases of errors nursing staff of (22) case. While the checklist distributed to a sample of nursing Angel Group in Sadr Teaching Hospital ’s (100) nurs According to the problem, the study in determining the responsibility of nursing staff for medical errors that are not important for the hospitals. Has shown results of the study agreement members of the study sample that the clarity of the power possessed by nursing staff at work and determine responsibility leads to reduce medical errors by the nursing staff The most important conclusions that the non-use of starters mandate effective authority for staff nursing leads to mistakes by the nursing staff and to determine the responsibility of nursing staff for medical errors lead to a reduced commission. Either the most important recommendations for greater coordination and convergence between the sections of the hospital towards the issue of errors nursing staff and work on exchange of information , and to create a system characterized by easy and rapid exchange of information and the need to educate nursing staff and those who work medical duties , responsibilities and obligations imposed by the laws that regulate this profession humanity